Biographies in Malayalam, 1084-2013: A Bibliometric Analysis - Suresh Kumar, P. K. (Journal of Information and Knowledge, 2015)
This study is to examine the quantitative growth of biographies in Malayalam mainly based on Malayalam Grantham Soochi published by Kerala Sahithya Academy, Thrissur. The latest version of Malayalam Grandha Soochi brought out in 2006 includes books published in Malayalam up to 2000. Since the present study covers biographies in Malayalam up to 2013 the data was also collected from two major libraries in Kerala such as Kerala University Library, Trivandrum and Kerala Sahitya Academy Library, Thrissur having comprehensive collection of Malayalam books. The specific objectives of the study are to analyse the quantitative growth of biographies in Malayalam, to identify the prominent contributors of Ma layalam biographies, to rank the publishers of Malayalam biographies, to examine geographical and subject wise distribution of publishers, to find the average size of the book with respect to the number of pages in different periods and to trace the change in average price of Malayalam biographies. The major findings of the study are the number of Malayalam biographies published in olden days are very few but the there is an increasing trend after the formation of Kerala State. There is an up and down growth in biographical source from 1084 to 2013. It is also revealed that males are the major contributors of the biographies in Malayalam. No author has more than 14 biographical books in his/her credit. Majority of the Malayalam biographies are small in size having below 100 pages. Even though tremendous changes happened in the publishing and printing technology in the later years, the average price of the books is increasing. Since the existing bibliographical tools in Malayalam are not reliable and up to date, it is suggested that State Central Library and State Library Council should take the initiative for compiling a comprehensive Malayalam bibliography with the cooperation of all major libraries and publishers in Kerala.